Big night (Rysher Entertainment, 1996)
The story of two brothers whose Italian restaurant is on the brink of bankruptcy. Their only chance for success is to risk everything they own on an extravagant feast for bandleader Louis Prima. But their big night is complicated by a lovers' triangle, a sneaky restaurant rival, and the hilarious perfection of chef Primo.